Food security and sustainability: a vulnerability/resilience framework for food systems: Presented at IARU Sustainability Science Congress - Global Challenges: Achieving Sustainability. Copenhagen (Denmark), 22-24 Oct 2014 - Allen, T.; Prosperi, P.; Cogill, Bruce; Peri, I.; Padilla, M. (International Alliance of Research Universities, 2014)
The Sustainability Science Congress puts focus on research related to global sustainability issues. This international and solutions orientated congress invites experts across disciplines to break down academic barriers and jumpstart a broader collaboration on sustainable solutions relevant for society. Also targeting businesses and policy makers, the congress aims to provide a platform for science-policy interface relevant for global challenges.